2014
DOI: 10.1111/ijfs.12480
|View full text |Cite
|
Sign up to set email alerts
|

Production of yellow wine from Camellia Oleifera meal pretreated by mixed cultured solid‐state fermentation

Abstract: Summary Camellia oleifera meal was evaluated to be a potential feedstock for the production of yellow wine (YW), and process conditions were investigated. In this study, C. oleifera meal was firstly pretreated using mixed cultured Bacillus subtilis and Aspergillus niger under solid‐substrate fermentation to degrade the tea saponin (TS) for the following YW fermentation. Response surface methodology helped evaluate the effects of the selected operating parameters, and the optimal condition at a fixed time of 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 21 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…; Chang et al . ). This indicates that the traditional Chinese solid‐state fermentation method has unique advantages.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Chang et al . ). This indicates that the traditional Chinese solid‐state fermentation method has unique advantages.…”
Section: Introductionmentioning
confidence: 97%
“…Studies have shown that jujubes are rich in sugar (Claus and Berglund 2005;Li et al 2007) and contain similar components as grapes, which are used for producing brandy. Daqu and solid-state fermentation are characteristic of Chinese traditional liquor production techniques (Zheng et al 2011) and have recently been used in the brewing of fruit wine, bringing unique flavors and improving the quality of production (Berradre et al 2009;Zhang et al 2013;Chang et al 2014). This indicates that the traditional Chinese solid-state fermentation method has unique advantages.…”
Section: Introductionmentioning
confidence: 99%